2020
DOI: 10.1515/astro-2020-0019
|View full text |Cite
|
Sign up to set email alerts
|

Seeding the Solar System with Life: Mars, Venus, Earth, Moon, Protoplanets

Abstract: In the space of the entire universe, the only conclusive evidence of life, is found on Earth. Although the ultimate source of all life is unknown, many investigators believe Earth, Mars, and Venus may have been seeded with life when these planets, and the sun, were forming in a galactic cluster of thousands of stars and protoplanets. Yet others hypothesize that while and after becoming established members of this solar system, these worlds became contaminated with life during the heavy bombardment phase when s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 403 publications
(290 reference statements)
1
2
0
Order By: Relevance
“…It is thus noteworthy that some of the cyanobacteria, fungi, and worm-like and cocoon-like structures presented in this paper bear a resemblance to putative fossilized specimens discovered in meteorites as discussed by Wainwright and Wickramasinghe [24]. It has also been reported that cyanobacteria, fungi, lichens, seeds, worms, insecta, crustaceans, and their eggs survive long term exposure to space outside the ISS, and in Mars-like environments, and could survive interplanetary transfer to Mars [15,26,[31][32].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…It is thus noteworthy that some of the cyanobacteria, fungi, and worm-like and cocoon-like structures presented in this paper bear a resemblance to putative fossilized specimens discovered in meteorites as discussed by Wainwright and Wickramasinghe [24]. It has also been reported that cyanobacteria, fungi, lichens, seeds, worms, insecta, crustaceans, and their eggs survive long term exposure to space outside the ISS, and in Mars-like environments, and could survive interplanetary transfer to Mars [15,26,[31][32].…”
Section: Discussionsupporting
confidence: 67%
“…(1) Life on primordial Earth and Mars may have originated on other more ancient worlds [23][24][25][26], and these forms of life, including viruses, contained in their genomes the same foundation genes [23,[27][28][29]: the "genetic seeds" from which arose and evolved similar forms of life on both planets.…”
Section: Why Specimens Are Similar To Those From Earth? Extraterrestr...mentioning
confidence: 99%
“…In addition, structures resembling stromatolites possibly constructed by photosynthesizing-oxygen-producing algae / cyanobacteria have been observed on Mars (Bianciardi et al 2014(Bianciardi et al , 2015Joseph et al 2019Joseph et al , 2020aRizzo 2020;Rizzo andCantasano 2009, 2016;Ruff and Farmer 2016) at least one of which is dated to 3.7 bya (Noffke 2015). Although it has been questioned if all micro-thromoboliteson Earth or Mars-are truly biological, eight of the Martian sedimentary-stromatolites structures, so far reported, are nearly identical to the concentric-domical stromatolites of Lake Thetis, Australia, and may range in age from a few thousand to a few million years (Joseph et al 2020c). Moreover, they were photographed in the presence of microbial mats and consist of numerous open-cone-apertures and fenestra (Joseph et al 2020a,c,d).…”
Section: Soil -Atmosphere Exchange and Abiogenic Oxygen?mentioning
confidence: 99%